Temporal stability of regional wage differentials in Brazil - William D. Savedoff (Institute for Applied Economic Research (ipea), 2015)
This paper focuses on regional differentials in income, and particulary wages. It discusses some of the explanations for these differentials, and their implications. Using evidence from several sources, the paper shows that regional wage different ials are highly stable in Braz i 1, raising quest ions about neo-classical theories of wage determination and lending support to structural and market segmentation theories.
Keywords: 330